Nse5/6 is a negative regulator of the ATPase activity of the Smc5/6 complex - Hallett, Stephen T; Schellenberger, Pascale; Zhou, Lihong; Beuron, Fabienne; Morris, Ed; Murray, Johanne M; Oliver, Antony W (Nucleic acids research, 2021)
Abstract The multi-component Smc5/6 complex plays a critical role in the resolution of recombination intermediates formed during mitosis and meiosis, and in the cellular response to replication stress. Using recombinant proteins, we have reconstituted a series of defined Saccharomyces cerevisiae Smc5/6 complexes, visualised them by negative stain electron microscopy, and tested their ability to function as an ATPase. We find that only the six protein ‘holo-complex’ is capable of turning over ATP and that its activity is significantly increased by the addition of double-stranded DNA to reaction mixes. Furthermore, stimulation is wholly dependent on functional ATP-binding pockets in both Smc5 and Smc6. Importantly, we demonstrate that budding yeast Nse5/6 acts as a negative regulator of Smc5/6 ATPase activity, binding to the head-end of the complex to suppress turnover, irrespective of the DNA-bound status of the complex.